Visual Citizenship Communicating political opinions and emotions on social media - Bouko, Catherine (Routledge Studies in Media, Communication, and Politics, 2024)
This book explores visual political engagement online - how citizens participate in the dynamism of life in society by expressing their opinions and emotions on various issues of democratic life in image-based social media posts, independently of collective actions. Looking beyond large digital social movements to focus on the everyday, the book provides a well-documented and comprehensive framework of key notions, concrete methods and examples of empirical insights into everyday visual citizenship on social media. It shows how the visual has become ubiquitous in citizens' communication on social media, focusing on how citizens use visual content to express their emotions and opinions on social media platforms when they discuss politics in a large sense. With this book, every reader interested in political communication, visual communication and/or new media is fully equipped to analyse everyday visual citizenship on social media platforms. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.